INTELLIGENT SOFTWARE CONTROL SYSTEM FOR A MULTI-AXIS VIRTUAL REALITY PLATFORM WITH SIMULATED ENVIRONMENTAL IMPACT AND FEEDBACK - Aleksandr D. Ivanov; Aleksandr Yu. Tychkov; Denis S. Chernyshov; Sofia Yu. Tverskaya; Ruslan V. Zolotarev; Mihail S. Yakovlev (Измерение, мониторинг, управление, контроль, 2023)
Background. The aim of the work is to create a prototype of software for hardware control of a new multiaxis platform for virtual reality with simulated environmental effects and feedback, providing a complete immersion of the user in virtual reality through exposure to sensory biological signaling systems (tactile, vestibular, auditory, visual). Materials and methods. As part of the implementation of this project, a software product has been created to control a multiaxis platform for virtual reality, providing full immersion of the user with simulated environmental impact and feedback. Results. The result of the project is a working prototype of the system.